1996
DOI: 10.1093/brain/119.1.295
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile limb-girdle muscular dystrophy

Abstract: A series of patients affected by a muscular dystrophy, similar to the original description of a juvenile scapulo-humeral form by Erb in 1884 and fitting with the criteria used to define limb-girdle muscular dystrophies, was discovered in a small community living in the southern part of Reunion Island in the Indian Ocean. A detailed clinical analysis was conducted over 5 years on a cohort of 20 patients. This community presented a high degree of consanguinity as it was segregated from the majority of the island… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(34 citation statements)
references
References 0 publications
3
28
0
3
Order By: Relevance
“…In terms of clinical presentation, our study confirms and further delineates the picture previously reported in several earlier studies 2, 3, 21, 22, 23, 24, 25, 26. Muscle weakness, which is remarkably symmetrical, is predominant in the axial muscles of the trunk and proximal muscles of the lower limb.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In terms of clinical presentation, our study confirms and further delineates the picture previously reported in several earlier studies 2, 3, 21, 22, 23, 24, 25, 26. Muscle weakness, which is remarkably symmetrical, is predominant in the axial muscles of the trunk and proximal muscles of the lower limb.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, patients carrying two null mutations that result in the premature truncation of protein synthesis are invariably characterized by a higher disease severity than patients with at least one missense mutation 2, 22, 34. Our study is no exception since, for a large number of parameters, the null mutations tend to lead not only to a more severe presentation, but we also observed that the M2 group corresponds to the less severe group (Table 2C).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…c.550delA mutation is the most common allele in Caucasian populations. [30] Founder effect for the c.550delA mutation has been demonstrated in the Eastern Mediterranean region (Russia, Croatia, Bulgaria, and Northern Italy)[313233343536373839404142] Other rare mutations which have a founder effect in small populations due to cultural inbreeding associated with historical, demographic, or religious factors have been reported in the population of La Reunion Island in the Indian Ocean (c.946-1G>A),[43] in the Old Order Amish community in Northern Indiana in the USA (c.2306G>A),[4445] in the Guipuzcoa region of the Basque Country of Spain and in Brazil (c.2362_2363delAGinsTCATCT),[464748] Japan (c.1795_1796insA),[495051] the Chioggia village in the Venetian lagoon (p.R490Q),[35] the Mocheni population in the Italian Alps (c.1193 + 6T>A),[52] and the Agarwal community in Northern India (p.D780H and c.2099-1G>T). [53] The last one is relevant to India and hence is discussed further.…”
Section: Calpainopathymentioning
confidence: 99%